Analisis Kinerja Tenaga Kontrak Bidang Informasi dan Teknologi (IT) pada Dinas Komunikasi dan Informatika Provinsi Sumatera Selatan - Ahsani, Deswan; Zuber, Konar; Hakim, Arif Rahman (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2024)
The South Sumatra Province Communication and Informatics Service plays an important role in the fields of communication, informatics, coding and statistics. With the vision of